Temporal Trends in Type 2 Diabetes Burden and Care Outcomes in Taiwan From 2012 to 2021: Nationwide Population-Based Cohort Study - Ming-Yen Lin; Yi-Ling Wu; Hsiaoting Wu; Chih-Cheng Hsu (JMIR Public Health and Surveillance, 2026)
Background Understanding temporal changes in noncommunicable diseases such as diabetes is crucial for informing health policy precisely and improving population-level outcomes. Objective This study aimed to evaluate temporal trends in key health metrics of type 2 diabetes using nationwide surveillance data to inform future prevention and care strategies in a resource-rich country. Methods We conducted a retrospective, population-based cohort study to analyze temporal trends in annual incidence, prevalence, mortality, and life expectancy from 2012 to 2021; the ABC (hemoglobin A1c [HbA1c], blood pressure, and cholesterol) control metrics from 2015 to 2021; and complication-specific incidence rates from 2017 to 2021. The selected health metrics were quantified overall and stratified by age and sex and standardized to understand disparities in trends. An autoregressive model was used to evaluate temporal change after appropriately accounting for serial correlation in the data. Results The standardized incidence and mortality rates of type 2 diabetes slightly declined, by an average of 0.029 (95% CI 0.011-0.047) and 0.043 (95% CI 0.011-0.076) per 100 patient-years annually, respectively (P=.006 and P=.02). These declines coincided with a significant average annual increase of 0.17 (95% CI 0.15-0.21) in the standardized prevalence proportion (P